(untitled) (SCIENCE TIME JOURNAL, 2026)
This article aims to substantiate the integrative approach, which has become necessary for application to all stages of education today, its initial introduction into pedagogy, its importance, and the need for its application to the educational process through theoretical foundations and practical guidelines.